PHYSIOLOGICAL RESPONSES AND TOLERANCE EFFICIENCY OF Spinacea oleracea L. UNDER HYDROPONIC Ni2+ STRESS CONDITION - Adulsalam, S.; Dagari, M. S.; Lami, H. O.; Ugbenya, N. o.; Yah, M. K.; Abdulsalami, H. (FUDMA JOURNAL OF SCIENCES, 2022)
An indoor EDTA and HNO3 enriched environment was created by an injection system with timing and varying concentration control. Spinacea oleracea was selected hydroponic plant exposed to various doses of Ni2+ (0, 1000, 2000 and 4000 mg/L) as Na2EDTA at (0, 500 and 3000 mg/L) and (0,500 and 3000 mg/L) HNO3 in different combinations for 6 days with 10-hour-treatment each day. This study used modified Hoagland nutrient culture in a screen house to provide an ideal environment for comparing the efficiency of chelate-assisted and unchelated phytoextraction of Ni2+ by S. oleracea. Changes in morphological characteristics including leaf damage rate to evaluate morphological resistance to Ni2+ uptake and proline contents was observed. Changes in fresh biomass were significant (p < 0.05) with respect to addition of EDTA and HNO3 at different concentration to different concentrations of Ni2+ compared to unchelated treatments of same concentrations of Ni2+. The Ni2+ induced proline accumulation in shoots increased significantly (P < 0.05) with increasing Ni2+ concentrations.